Exploring the challenges of sustainable procurement implementation: insights from Botswana’s public sector - Kuruneri, Joseph (Frontiers in Sustainability, 2025)
IntroductionSustainable procurement (SP) is increasingly recognized as a strategic tool for addressing environmental (e.g., carbon emissions, pollution), social (e.g., unemployment, discrimination), and economic (e.g., inequality, poor SME support) challenges in developing countries such as Botswana. Despite the public sector’s significant purchasing power, persistent implementation barriers continue to limit the potential of SP, necessitating further investigation into these challenges.MethodsThis study explored SP implementation barriers from the perspective of procurement personnel. Data were collected through semi-structured interviews with 15 participants selected using convenience sampling. Thematic analysis was applied to identify key patterns and insights from the qualitative data.ResultsThe study reveals three underexplored barriers in the SP literature: undue pressure from political leaders, ineffective government payment systems, and weak reporting channels. Five broader challenge domains emerged: resource constraints, policy constraints, monitoring and evaluation gaps, cultural resistance, and political interference. Notably, institutional barriers (policy, monitoring, cultural, and political) dominated, representing 7 out of 10 subthemes, whereas resource-related barriers accounted for only 3.DiscussionThe findings highlight systemic institutional vulnerabilities that hinder SP implementation, underscoring the need for governance reforms alongside financial and capacity-building investments. Proposed mitigation strategies include revising procurement policies, implementing modern e-payment systems, offering supplier incentives (e.g., tax breaks), improving reporting structures, and enhancing stakeholder collaboration. These insights provide a comparative baseline for future studies and inform policy reforms aimed at overcoming SP implementation barriers in Botswana.